Riwayat Pemberian ASI Eksklusif Dengan Kejadian Stunting - Dwi Ertiana (STIKES dan AKZI Karya Husada Kediri, 2024)
Stunting is one of the problems that inhibits the development and growth of toddlers globally. Malnutrition at an early age will increase infant and child mortality rates, and cause sufferers to get sick easily and have less than optimal body posture as adults. One of the causes of stunting is the provision of Exclusive Breastfeeding. The purpose of this study was to describe the history of exclusive breastfeeding with the incidence of stunting in toddlers aged 7-24 months at the Campurdarat Health Center, Tulungagung Regency in 2023. The type of research used was descriptive research. The research variables were Exclusive Breastfeeding and Stunting Incidence. The study was conducted at the Campurdarat Health Center, Tulungagung Regency on October 6-12, 2023. The population of all toddlers aged 7-24 months at the Campurdarat Health Center, Tulungagung Regency was 986 respondents. The sampling technique used was proportional random sampling. With a sample size of 124 respondents. The results of the analysis showed that out of 72 respondents (58.1%) with a history of toddlers being given Exclusive Breastfeeding, all of them did not experience stunting. Meanwhile, in 52 respondents (41.9%) who were not given exclusive breastfeeding, 14 respondents (11.3%) experienced stunting, and 38 respondents (30.6%) were not stunted. Toddlers who do not get enough breast milk have poor nutritional intake which will hamper the growth and development of toddlers. Therefore, providing exclusive breastfeeding to babies can reduce the possibility of stunting in toddlers.